In Vitro CYTOTOXIC ASSAY OF CHLOROFORM EXTRACT OF Brucea javanica L .(Meer), Ipomoea batatas Poir., Mussaenda pubescens Ait.F., AND Portulaca oleracea L. TO HeLa CELLS - M, Sonlimar; ., Sismindari; ., Mustofa (Indonesian Journal of Pharmacy, 2002)
Some plants, such as Ipomoea batatas Poir., Mussaenda pubescens Ait. F., Portulaca oleracea L., Brucea javanica L. (Meer), have been used traditionally to treat cancer, even though the scientific base of this activity has yet been completely investigated. The study was conducted to evaluate the cytotoxic activity of these plants on HeLa cell lines.The cytotoxicity of chloroform extract from these plants were determined using micro radioactive method by measuring an incorporation (3H)-hipoxanthine on the cells after 24 and 48 hours incubation with each extract, using doxorubicine as a positive control. Extract free cell culture was refered to as 100% growth. IC50 value, showing 50% inhibition of the cell growth, was determined based on the concentration versus percentage inhibition curves.The result showed the extract B. javanica was the most active to hela cells with the IC50 value of 13.69 ï‚±1.07 and 55.7ï‚±8.4 ïg/ml after 24 and 48 hours incubation respectively.Key words: Ipomoea batatas Poir., Mussaenda pubescens Ait. F., Portulaca oleracea L., Brucea javanica L. (Meer), Cytotoxic, HeLa cell lines.